The Women in ORTHopaedics Program Offers Early Exposure to Orthopaedic Surgery for Young Women. A Pre- and Post-Event Survey Comparison - Marianna Hsu, BSc candidate; Hayley Spurr, MB, BCh, BAO, FRCSC; Anthony P. Cooper, MBChB, FRCSC; Emily K. Schaeffer, PhD (Journal of the Pediatric Orthopaedic Society of North America)
Background: In recent years, the medical field has made significant progress toward promoting gender equality. Despite this progress, orthopaaedic surgery remains the least diverse specialty among other surgical specialties. In response, our Department of Orthopaedics developed a specialized orthopaedic curriculum, Women in ORTHopaedics (WORTH), tailored specifically for young women in high school. This program offers early exposure and mentorship opportunities within the orthopaedic field. Methods: Participants were asked to complete a preliminary survey prior to the workshop. Subsequently, a corresponding survey was administered following the workshop, mirroring the questions from the pre-event survey. Participants shared their impressions of orthopaedics, interest in pursuing a career in this field, and awareness of available career pathways within this specialty. Results: In both workshops, the consensus among participants in the pre-event surveys included a sense of novelty and a desire to learn more about orthopaedics. However, post-workshop responses revealed a shift in perceptions, with participants expressing that orthopaedics encompasses a much broader array of subjects than initially expected. A comparison between pre- and post-survey responses indicates a heightened interest in pursuing a career in orthopaedics following the workshop. Additionally, 100% of attendees expressed their intention to participate in future WORTH events. Conclusions: Findings indicate that WORTH played a constructive role in guiding young women toward trajectories beyond secondary education. Additionally, it provided insights into the multitude of career options available in Orthopaedics apart from surgery, including physiotherapy, occupational therapy, nursing, research, and biomedical engineering. Key Concepts: (1) Early exposure and mentorship allow for increased representation and retention of women in orthopaedics. (2) Representation of women in orthopaedics improves patient care and contributes to a more holistic approach to healthcare. (3) Outreach initiatives influence participants' interest and perceptions of pursuing a career in orthopaedics. Level of Evidence: Level IV